Islamization Of Knowledge In Qur’anic Perspective - M. Thoriqul Islam; Elvan Tedio Fawaz (Studia Quranika, 2017)
Islamization is a discipline that describes the form of the character and Islamic identity as a way of life or worldview in which there is an integral view of the concept of knowledge (epistemology) and the concept of God (theology). In Islam, knowledge is formed and sourced from the Islamic view of life, which is closely related to the basic structure of the metaphysics of Islam that has formulated in-line with revelation, tradition, reason, experience and intuition. Formation of those through the educational process. However, due to the influence of western worldview through westernization and globalization, Islamic education lost its role in linking science with Islamic view of life. Therefore, the muslim scholars, among others, Ismail al-Faruqi in his "Islamization of Knowledge: General Principles and Workplans" and Naquib al-Attas in his "Islam and Secularism" that initiated the Islamization of science, are determined to restore science having judged it to have its axiology misrepresented. In perspective of the Quran, the Islamization of science described in Sura al-Fathir 35/28, Islamization actually leads to faith, faith related to instinct, while science to adjust to the surrounding situation. Truly, Allah is The almighty.